1989
DOI: 10.1038/clpt.1989.22
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive control of etoposide administration: Impact of interpatient pharmacodynamic variability

Abstract: We sought to use a previously derived pharmacodynamic model for 72-hour etoposide infusions to adaptively control administration of this agent and to demonstrate that more predictable toxicity could be obtained with this dosing scheme. A randomized crossover study design was used to compare "standard" dosing (125 mg/m2/day) to adaptive control, with dose adjustment at 28 hours based on the 24-hour plasma level. A total of 31 patients received 86 cycles of chemotherapy, 36 by standard dosing and 50 by adaptive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

1997
1997
2009
2009

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(19 citation statements)
references
References 1 publication
0
19
0
Order By: Relevance
“…This approach has yielded a decrease in intrapatient and interpatient variability in haematological toxicity in patients treated with i.v. etoposide [40,41]. TDM-guided dose individualization of methotrexate, teniposide and cytarabine has permitted the safe increase drug exposure in children with leukaemia [42], resulting in a signi®cant improvement in disease free as compared with conventional therapy.…”
Section: Discussionmentioning
confidence: 99%
“…This approach has yielded a decrease in intrapatient and interpatient variability in haematological toxicity in patients treated with i.v. etoposide [40,41]. TDM-guided dose individualization of methotrexate, teniposide and cytarabine has permitted the safe increase drug exposure in children with leukaemia [42], resulting in a signi®cant improvement in disease free as compared with conventional therapy.…”
Section: Discussionmentioning
confidence: 99%
“…This patient had a [5LCr]EDTA clearance, which was at the bottom of the normal range (59 ml min-' m-2) and the longest [5'Cr]EDTA elimination half-life (114 min vs 77±23 min), although no overt signs of renal impairment. It seems likely that the reduced interpatient pharmacokinetic variability seen in this group of patients was due to the fact that only one child had previously received cisplatin, as cisplatin therapy has previously been shown to predict for reduced etoposide clearance (Pfluger et al, 1987(Pfluger et al, , 1993Relling et al, 1994 Previous studies involving targeted dosing with etoposide using limited sampling methods have involved the administration of etoposide as a continuous infusion over 3 or 5 days (Ratain et al, 1989(Ratain et al, , 1991Joel et al, 1996). In addition, English et al (1996) reported two anephric paediatric patients in whom targeted dosing with both etoposide and carboplatin was possible using detailed pharmacokinetic sampling over three doses.…”
Section: Discussionmentioning
confidence: 99%
“…Adaptive control of etoposide dosing based upon both pharmacokinetic and pharmacodynamic factors has been used by Ratain et al (1989Ratain et al ( , 1991 to treat patients with small-cell lung cancer. In these latter studies, dosing in the adaptive control arm was based upon the pretreatment white cell count and the plasma etoposide concentration at 24 h, and the pharmacodynamic target was a chosen degree of haematological toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…One approach to reduce this variability would be through adaptive control dosing strategies, in which drug concentrations are determined during or after drug administration, and subsequent doses adjusted to achieve a target concentration or drug exposure. That strategy has been effectively used for many regimens including etoposide, 47 topotecan, 48 and antimetabolites. 49 Unfortunately, generalized application of these approaches is limited by necessity for specialized personnel to perform drug quantitation and pharmacokinetic modeling.…”
Section: Figurementioning
confidence: 99%